PERAN MEDIASI MOTIVASI KERJA PADA HUBUNGAN KOMPENSASI, LINGKUNGAN KERJA, BEBAN KERJA, DAN KINERJA DI PUSKESMAS SELAYO KECAMATAN KUBUNG KABUPATEN SOLOK - Shakyla Aprisonia A; Zefriyenni; Jhon Veri (Journal Publicuho, 2025)
This study aims to examine the effect of compensation, work environment, and workload on performance mediated by work motivation. A quantitative approach with hypothesis testing techniques was used in this study. There were 80 samples with the saturated sample technique, namely, all employees at the Selayo Health Centre, West Sumatra. Data were collected through distributing questionnaires online and processed using SmartPLS 3.0 software with structural equation modelling techniques. The results showed that work environment and workload each had a positive and significant effect on work motivation, but compensation was found to have an insignificant effect. The work environment and work motivation each have a positive and significant effect on performance, but found insignificant influence by compensation and workload. The effect of work environment and workload on performance through the mediation of work motivation was found to be positive and significant, but insignificant mediation by work motivation on the relationship between compensation and performance was found. The implications of the study emphasise the importance of maintaining the commitment and morale of employees in health agencies to provide the best service to patients.